Palpable Mass on the Head after Minor Trauma. (10th November 2016) - Nikolakopoulos, K. M.; Papageorgopoulou, C. P.; Ntouvas, I. G.; Kakkos, S.; Tsolakis, I.
Abstract : Temporal artery is superficially exhibited and easily traumatized. Rarely, a minor and blunt trauma, especially in elderly who are under anticoagulants, can cause a pseudoaneurysm. Diagnosis should be based, primarily, on history and physical examination and secondarily on duplex ultrasound scanning which will lead to confirmation and preoperative planning. The therapeutical plan consists of surgical ligation and excision of the aneurysm. Surgery can be performed under local anesthesia with no postoperative major or minor complications. Endovascular approach consists of catheter embolization and remains a second option due to the risk of complications and the inconclusive results. On this review, authors present a case of an 80-year-old male with a pseudoaneurysm of superficial temporal artery.